Household Food Security Of Porang Farmers In Surakarta Buffer Districts - Rosita Dewati; Agung Setyarini; Yos Wahyu Harinta; Yoesti Silvana Arianti; Novian Wely Asmoro; Sifa Aulia Wicaksari; Wahyu Adhi Saputro (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Farmers are the majority of jobs of Indonesian people, including porang farmers in the Surakarta buffer district. The existence of porang farmers has begun to be shaken in recent times due to quite extreme climate change, so it is feared that in addition to affecting the production of porang farmers, it will also have an impact on the food security of porang farmer households in the Surakarta buffer district. This study aimed to determine the food security level of porang farmer households in the three Surakarta buffer districts: Sukoharjo, Wonogiri, and Karanganyar. Food security analysis is a cross between the share of food expenditure and the caloric adequacy percentage, analyzed using the Jonsson and Toole cross-classification method. The analysis showed that based on the value of the share of food expenditure, 88% of porang farmers were in a food-secure condition, and the remaining 12% were in a food-insecure condition. The average portion of porang farmers' food expenditure was 40.36%. The results of the AKE calculation show that porang farmers consume energy of 2,937 kcal/capita /day. Based on Jonsson and Toole's cross-classification, about 76% of porang farmers are in the food secure category, 12% are in the food vulnerable category, and the remaining 12% are in the food less secure category; no farmers are in the food insecure category. This study's findings are crucial as they demonstrate that despite climate variability and fluctuating price changes, porang farmers in the Surakarta buffer district are classified as food-secure.